Continental Interior and Edge Breakup at Convergent Margins Induced by Subduction Direction Reversal: A Numerical Modeling Study Applied to the South China Sea Margin. Issue 11 (30th October 2020) - Li, Fucheng; Sun, Zhen; Yang, Hongfeng; Lin, Jian; Stock, Joann M.; Zhao, Zhongxian; Xu, Hehua; Sun, Longtao
Abstract: The dynamics of continental breakup at convergent margins has been described as the results of backarc opening caused by slab rollback or drag force induced by subduction direction reversal. Although the rollback hypothesis has been intensively studied, our understanding of the consequence of subduction direction reversal remains limited. Using thermo‐mechanical modeling based on constraints from the South China Sea (SCS) region, we investigate how subduction direction reversal controls the breakup of convergent margins. The numerical results show that two distinct breakup modes, namely, continental interior and edge breakup ("edge" refers to continent above the plate boundary interface), may develop depending on the "maturity" of the convergent margin and the age of the oceanic lithosphere. For a slab age of ~15 to ~45 Ma, increasing the duration of subduction promotes the continental interior breakup mode, where a large block of the continental material is separated from the overriding plate. In contrast, the continental edge breakup mode develops when the subduction is a short‐duration event, and in this mode, a wide zone of less continuous continental fragments and tearing of the subducted slab occur. These two modes are consistent with the interior (relic late Mesozoic arc) and edge (relic forearc) rifting characteristics in the western and eastern SCS margin, suggesting that variation in the northwest‐directed subduction duration of the Proto‐SCS might be a reason for the differential breakup locus along the strike of the SCS margin. Besides, a two‐segment trench associated with the northwest‐directed subduction is implied in the present‐day SCS region. Key Points: The drag force induced by subduction direction reversal can invoke the continental breakup at continental convergent margins Continental interior and edge breakup modes develop depending on the "maturity" of the convergent margins and the oceanic lithosphere age Variation in the northwest‐directed subduction of the PSCS is a reason breaking the relic arc and forearc along the strike of the SCS margin